2022
DOI: 10.3390/vaccines10111781
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Adverse Effects Following Booster Dose of Inactivated-Virus vs. Adenoviral-Vector COVID-19 Vaccines in Algeria: A Cross-Sectional Study of the General Population

Abstract: COVID-19 booster vaccines have been adopted in almost all countries to enhance the immune response and combat the emergence of new variants. Algeria adopted this strategy in November 2021. This study was conducted to consider the self-reported side effects of COVID-19 booster vaccines by Algerians who were vaccinated with a booster dose of one of the approved inactivated-virus vaccines, such as BBIBP-CorV and CoronaVac, or one of the adenoviral-vector-based vaccines, such as Gam-COVID-Vac, AZD1222 and Ad26.COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
6
12
0
Order By: Relevance
“…Literature supports this finding since two other studies found that all participants had adverse effects after the first booster dose [20,21]. Other studies found also high prevalence of adverse effect after the first booster dose ranging from 74.7% to 89% [14][15][16][17]22,23]. Slight differences in prevalence of adverse effects among studies could be attributed to different study designs, populations, and definitions.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 79%
See 1 more Smart Citation
“…Literature supports this finding since two other studies found that all participants had adverse effects after the first booster dose [20,21]. Other studies found also high prevalence of adverse effect after the first booster dose ranging from 74.7% to 89% [14][15][16][17]22,23]. Slight differences in prevalence of adverse effects among studies could be attributed to different study designs, populations, and definitions.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 79%
“…To our knowledge, our study investigated for first time the relationship between severity of COVID-19 symptoms and adverse effects and thus a direct comparison with other studies could not be feasible. However, it is well known that adverse effects are more common among individuals with a history of COVID-19 or/and past exposure to SARS-CoV-2 not only after the primary vaccination [24][25][26] but also after the first booster dose [16,20]. Repeated COVID-19 vaccine doses can induce more adverse effects due to cytokine production especially in people who had previously been infected with SARS-CoV-2 [27].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…It is also important to note that some studies conducted in Algeria have reported adverse events following vaccinations. These adverse events ranged from mild side effects such as pain or swelling at the injection site, to more serious side effects such as fever or allergic reactions [15][16][17]. Additionally, one of the studies reported that some individuals have regretted receiving the vaccines [17].…”
Section: Challenges and Progress Toward Herd Immunitymentioning
confidence: 99%
“…The Coronavirus disease 2019 (COVID-19) pandemic has exerted long-lasting impacts on multiple domains of health (1)(2)(3). The first COVID-19 case was identified in Wuhan, China in December 2019 (4,5).…”
Section: Introductionmentioning
confidence: 99%